Novel type of pilus associated with a Shiga-toxigenic E. coli hybrid pathovar conveys aggregative adherence and bacterial virulence. Issue 1 (December 2018) - Lang, Christina; Fruth, Angelika; Holland, Gudrun; Laue, Michael; Mühlen, Sabrina; Dersch, Petra; Flieger, Antje
Abstract A large German outbreak in 2011 was caused by a locus of enterocyte effacement (LEE)-negative enterohemorrhagicE. coli (EHEC) strain of the serotype O104:H4. This strain harbors markers that are characteristic of both EHEC and enteroaggregativeE. coli (EAEC), including aggregative adhesion fimbriae (AAF) genes. Such rare EHEC/EAEC hybrids are highly pathogenic due to their possession of a combination of genes promoting severe toxicity and aggregative adhesion. We previously identified novel EHEC/EAEC hybrids and observed that one strain exhibited aggregative adherence but had no AAF genes. In this study, a genome sequence analysis showed that this strain belongs to the genoserotype O23:H8, MLST ST26, and harbors a 5.2 Mb chromosome and three plasmids. One plasmid carries some EAEC marker genes, such asaatA and genes with limited protein homology (11–61%) to those encoding the bundle-forming pilus (BFP) of enteropathogenicE. coli . Due to significant protein homology distance to known pili, we designated these as aggregate-forming pili (AFP)-encoding genes and the respective plasmid as pAFP. Theafp operon was arranged similarly to the operon of BFP genes but contained an additional gene, afpA2, which is homologous toafpA . The deletion of theafp operon, afpA, or a nearby gene (afpR ) encoding an AraC-like regulator, but notafpA2, led to a loss of pilin production, piliation, bacterial autoaggregation, and importantly, a >80% reduction in adhesion and cytotoxicity toward epithelial cells. Gene sets similar to theafp operon were identified in a variety ofaatA -positive but AAF-negative intestinal pathogenicE. coli . In summary, we characterized widely distributed and novel fimbriae that are essential for aggregative adherence and cytotoxicity in a LEE-negative Shiga-toxigenic hybrid.